Métodos de superação da dormência e temperatura na germinação de sementes de dioclea violácea - Zucareli, Valdir [UNESP]; Esteves Amaro, Amanda Cristina [UNESP]; Silverio, Evandro Vargas [UNESP]; Ferreira, Gisela [UNESP] (Universidade Estadual de Londrina (UEL), 2010)
The aim of this experiment was to overcome the dormancy and the effect of different temperatures in Dioclea violacea seeds' germination. Two experiments were developed. In the first, it was studied the use of chemical and mechanical scarification in the overcome dormancy seeds. Therefore, were accomplished seven treatments with four replications of 15 seeds each. The experiment constituted of one testify treatment, five chemical scarification treatments (1, 2, 3, 4 and 5 hours of immersion in concentrated sulfuric acid - H(2)SO(4)) and one mechanical scarification treatment. In the second experiment, was studied the temperature effects on germination seeds; it was constituted on six treatments with four replications with 12 seeds each. The treatments constituted of constant temperatures 15 degrees C, 20 degrees C, 25 degrees C, 30 degrees C and 35 degrees C and the alternate temperature 20-30 degrees C ( 16 and 8 hours, respectively). Germination, died seeds, hard seeds percentages, medium time germination and germination speed index were determined. The data were submitted to the variance analysis, and the averages compared by the Tukey test to 5% of probability and regression analysis. It was observed that the dormancy overcome of Dioclea violacea seeds can be done with chemical scarification, 3 to 5 hours in H(2)SO(4), as much as with mechanical scarification. Also, it was possible to conclude that Dioclea violacea seeds germinate in a wide temperature strip, with constant temperatures of 20 degrees C, 25 degrees C and 35 degrees C benefit the germination process.
Overcoming dormancy and different temperatures in Dioclea violacea seeds' germination
Keywords: Lianas; fabaceae; scarification